2016
DOI: 10.4238/gmr15049017
|View full text |Cite
|
Sign up to set email alerts
|

Association between -174G/C and -572G/C interleukin 6 gene polymorphisms and severe radiographic damage to the hands of Mexican patients with rheumatoid arthritis: a preliminary report

Abstract: ABSTRACT. Several interleukin 6 gene (IL6) polymorphisms are implicated in susceptibility to rheumatoid arthritis (RA). It has not yet been established with certainty if these polymorphisms are associated with the severe radiographic damage observed in some RA patients, particularly those with the development of joint bone ankylosis (JBA). The objective of the present study was to evaluate the association between severe radiographic damage in hands and the -174G/C and -572G/C IL6 polymorphisms in Mexican Mesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Locally acting on synoviocytes and osteoclasts in rheumatoid arthritis, IL-17A strengthens the connection between synoviocytes and joint deterioration [44]. In RA patients, IL-17 expression was found to be increased by Mahmood et al The study also divided the patients into groups based on the amounts of DAS-28 and ACCP antibodies in their bodies.…”
Section: Interleukin-17 Gene Polymorphismmentioning
confidence: 87%
“…Locally acting on synoviocytes and osteoclasts in rheumatoid arthritis, IL-17A strengthens the connection between synoviocytes and joint deterioration [44]. In RA patients, IL-17 expression was found to be increased by Mahmood et al The study also divided the patients into groups based on the amounts of DAS-28 and ACCP antibodies in their bodies.…”
Section: Interleukin-17 Gene Polymorphismmentioning
confidence: 87%
“…Different studies have examined the effect of IL-6 SNP and/or IL-8 SNP on diseases' risk, activity, and progression. Results showed marked ethnicity-associated disparities and diverse findings [12,[16][17][18][19][20][21][22][23]. For instance, a meta-analysis of European and Asian studies on IL-6 SNP and rheumatoid arthritis (RA) risk showed that IL-6 SNP was significantly associated with RA in Asian patients but not in the Caucasian population [20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a meta-analysis of European and Asian studies on IL-6 SNP and rheumatoid arthritis (RA) risk showed that IL-6 SNP was significantly associated with RA in Asian patients but not in the Caucasian population [ 20 ]. Another study has reported a strong association between IL-6 SNP and hand joint damage among Mexican patients [ 19 ]. In addition, vitamin D receptor (VDR) rs7975232 SNP was reported to predict PCa risk in African American men [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Another IL6 SNP (IL6 -572 : G/C) has also been investigated and its association with RA susceptibility or severity has been suggested in patients of different ethnicities. 14,15 The AG genotype of IL6 rs184229712 SNP was observed to be significantly associated with an increased expression of IL6 gene compared to GG genotype; therefore, it is suggested that such SNP may influence the gene expression of IL6 and subsequently its serum level in RA patients. The IL6 -174 and IL6 -572 SNPs have also been suggested to exert an influence on the transcription rate of IL-6 protein, and may influence IL-6 serum level in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Additional findings indicated that IL6 -174 SNP is associated with severe joint radiographic damage, while IL6 -572 showed no such association. 15 Accordingly, this study was conducted to assess gene expression and six SNPs (rs1800796 C/G, rs7802307 A/C/T, rs7802308 A/T, rs36215814 A/G, rs184229712 A/G and rs867254801 C/G) of IL-6 in etanercept-treated RA Iraqi Arab patients, with some emphases on disease activity, as well as clinical and laboratory markers of disease.…”
Section: Introductionmentioning
confidence: 99%